2017
DOI: 10.18203/issn.2454-5929.ijohns20170360
|View full text |Cite
|
Sign up to set email alerts
|

Overview of tympanoplasty techniques and results

Abstract: <p>The objective of this article is to overview about the changing techniques of tympanoplasty surgery and increase in the anatomical and functional success rate of surgeries. Introduction of endoscope in ear surgeries is time saving. Endoscopes are helpful to access hidden areas which was difficult with the help of microscope such as facial recesses, sinus tympani, extension of posterior-superior retraction pockets, etc. Also various modifications done in the techniques of using graft material for tympa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…In our study the mean age group of patients was 31 to 45 years which is similar to the study by Chavan et al, a retrospective study on 50 patients who underwent ossiculoplasty in the Department of ENT at a tertiary care hospital that had mean age in the 3 rd decade. 6 In our study out of 20 patients 13 were male and 7 female which is comparable to the study by Chavan et al a prospective study on 80 patients who underwent various type of ossiculoplasties wherein male preponderance was observed. 7 In our study, the long process of incus was eroded in 17 out of 20 cases and malleus was eroded in 2 out of 20 cases and malleus with incus eroded in 1 case, which is comparable to the study by Chavan et al in which long process of incus was the most susceptible part of the ossicular chain, affected due to the disease process in 74 patients, followed by the stapes in 29 patients with the malleus being the most resistant amongst the three, being affected in only 10 cases.…”
Section: Discussionsupporting
confidence: 88%
“…In our study the mean age group of patients was 31 to 45 years which is similar to the study by Chavan et al, a retrospective study on 50 patients who underwent ossiculoplasty in the Department of ENT at a tertiary care hospital that had mean age in the 3 rd decade. 6 In our study out of 20 patients 13 were male and 7 female which is comparable to the study by Chavan et al a prospective study on 80 patients who underwent various type of ossiculoplasties wherein male preponderance was observed. 7 In our study, the long process of incus was eroded in 17 out of 20 cases and malleus was eroded in 2 out of 20 cases and malleus with incus eroded in 1 case, which is comparable to the study by Chavan et al in which long process of incus was the most susceptible part of the ossicular chain, affected due to the disease process in 74 patients, followed by the stapes in 29 patients with the malleus being the most resistant amongst the three, being affected in only 10 cases.…”
Section: Discussionsupporting
confidence: 88%
“…Regular control after tympanomastoidectomy prevents reperforation from Chavan et al, 8 Kumar et al, 9 and Previous research by Tao et al 10 found that temporal graft fascia has more advantages such as being easier to extract, more quantity, relatively transparent, thinner and more flexible, but its elasticity strength as a low tympanic membrane makes it far more susceptible to negative pressure from the middle ear. Based on the background above, this study aims to determine changes in the image of tympanogram and audiogram postoperative tympanomastoidectomy using deep temporalis muscular graft fascia and composite graft.…”
Section: Introductionmentioning
confidence: 99%